Large cell/anaplastic medulloblastoma with myogenic, melanotic and neuronal differentiation: A case report of a rare tumor - Amany A. Fathaddin; Eman A. Bakhash; Abdulrahman J. Sabbagh; Sadeq W. Al-Dandan (Wolters Kluwer Medknow Publications, 2014)
Medulloblastoma is an embryonal neuroepithelial tumor of the cerebellum and is the most common malignant central nervous system tumor in children. Different histological variants and patterns have been described. The classic variant represents the majority of cases. This report describes a rare case of large cell/anaplastic medulloblastoma with myogenic, melanotic and neuronal differentiation arising in the cerebellum of a 3-year-old boy who presented with headache and vomiting. Magnetic resonance imaging demonstrated a heterogeneously enhanced lesion in the fourth ventricle. Surgical resection of the tumor was accomplished, but a residual tumor was left behind because of the involvement of the brainstem. Postoperatively, the patient received chemotherapy and radiotherapy. Currently, 20 months after treatment, the patient has survived without further progression. Pathological examination revealed a high grade primitive neuronal tumor with foci of myogenic features, melanin containing epithelial elements and ganglion-like cells, which were confirmed by immunohistochemistry.